Treatment of Infiltrative Superficial Tumors in Awake Standing Horses Using Novel High-Frequency Pulsed Electrical Fields - Byron, Christopher R.; DeWitt, Matthew R.; Latouche, Eduardo L.; Davalos, Rafael V.; Robertson, John L. (Frontiers in Veterinary Science, 2019)
Irreversible electroporation is a proven ablation modality for local ablation of soft tissue tumors in animals and humans. However, the strong muscle contractions associated with the electrical impulses (duration, 50-100 μs) requires the use of general anesthesia and, in most situations, application of neuromuscular blockade. As such, this technology is not used in an outpatient setting for ablating common cutaneous tumors (e.g., squamous cell carcinoma or melanoma) in humans or animals. Recently, high-frequency irreversible electroporation (H-FIRE) technology has been developed to enable electroporation of tumors without stimulation of nearby skeletal muscle. H-FIRE administers bursts of electrical pulses (duration, 0.5-2 μs) through bipolar electrodes placed in tumor parenchyma. We hypothesized that H-FIRE could be used to safely ablate superficial tumors in standing, awake horses without the need for general anesthesia. Here, we describe the treatment of superficial tumors in five horses using this novel ablation therapy without the need for general anesthesia. In each case, H-FIRE therapy predictably ablated tumor volume. All patients tolerated the procedure, no complications developed, and veterinary personnel safety was maintained. The H-FIRE treatment may be useful for treatment in veterinary and human patients in an outpatient setting without the need for hospitalization, general anesthesia, and advanced monitoring techniques.